Treatment Results of Fractures of the Lower Humerus in Adults - Tomonaga, Tadashi; Horiuchi, Hidehiko; Rabbi, M. E.; Itoh, Nobuyuki; Etoh, Masao; Hara, Hironori (Orthopedics & Traumatology, 1998)
Seventeen cases with fractures of the lower end of the humerus in adults were studied. Subjects consisted of 11 males, 6 females with a mean age of 35.5 years. We treated 1 case conservatively, 16 cases surgically. Patients who started active ROM exercise early after injury gained a wide ROM of the elbow and achieved satisfactory results in ADL. We recommend rigid fixation and early movement to achieve a satisfactory result.